ANALISIS TOTAL SULFUR TERHADAP SAMPEL FEED GAS DENGAN MEMBANDINGKAN STANDAR GAS DAN STANDAR LIQUID MENGGUNAKAN METODE TS-100V - Eko Haryanto; Rahmat Gunawan; Chairul Saleh (JURNAL KIMIA MULAWARMAN, 2014)
The total sulfur analysis in the feed gas sample by using standard gas and liquid has been researched. The concentration of total sulfur obtained from a calibration curve by using standard gas or liquid by TS - 100V. Based on the analysis of measurement linearity, by making curve a linearity from a standard gas H 2 S was 0.999 and standard liquid dibutyl sulfide was 0.998, where both the standard curve can be as a calibration curve because each the value of the correlation coefficient (r) having worth >0.995. Based on the analysis of measurement precision namely repeatability by measuring a feed gas sample train G as many as 5 times been gained. RSD value was 4.17 in standard gas and 4.70 in standard liquid. Both the calibration curve has been accepted because the relative standard deviation values less than 0.67 from Horwitz and still into get allowed range values from 7.3 to 11%. Based on the analysis of accuracy’s measurement is percent recovery for the standard gas was 100.578% and for standard liquid was 104.380%. Both of them has been accepted because it still fit in the allowed range values 80-110%.Keywords : Total Sulfur, H 2 S Standard Gas, Standard Liquid Dibutyl Sulphites and TS-100V